Perancangan Platform Internet of Things sebagai Sistem Komunikasi Dua Arah untuk Pemantauan pH Air - Joniwarta; Prio Kustanto; Ridwan (Journal of Informatic and Information Security, 2025)
Water quality monitoring is a critical component in ensuring environmental sustainability and public health. The degree of acidity (pH) is one of the key parameters used to assess water quality, as it directly affects the suitability of water for domestic and industrial applications. Conventional water pH measurement systems are typically local and rely on manual data recording, resulting in limited data accessibility, susceptibility to human error, and the absence of structured historical records. This study presents the design of an Internet of Things (IoT) platform as a two-way communication system between water pH sensing hardware and a cloud-based digital platform. The proposed system consists of a pH sensor, a network-enabled microcontroller, a cloud platform for centralized data management, and a web-based dashboard as the user interface. Two-way communication enables the system not only to transmit real-time measurement data but also to receive configuration commands from users. Experimental results indicate that the proposed IoT platform improves the efficiency of water pH monitoring, reduces reliance on manual data recording, and provides structured historical data to support long-term analysis.